2017
DOI: 10.1128/microbiolspec.mtbp-0013-2016
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Transmission of Antibiotic-Resistant Bacteria

Abstract: Ever since antibiotics were introduced into human and veterinary medicine to treat and prevent bacterial infections there has been a steady selection and increase in the frequency of antibiotic resistant bacteria. To be able to reduce the rate of resistance evolution, we need to understand how various biotic and abiotic factors interact to drive the complex processes of resistance emergence and transmission. We describe several of the fundamental factors that underlay resistance evolution, including rates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 448 publications
(459 reference statements)
1
48
0
Order By: Relevance
“…Although very little data are available regarding sources, mechanisms, or frequencies of ARG transfer between clinical reservoirs (Andersson and Hughes 2017), there are multiple cases in which the same ARG has been detected simultaneously on hospital surfaces and in patients (Hota et al 2009;Lowe et al 2012;Conlan et al 2014). Recently, the rate of bla OXA-48 plasmid transfer between Klebsiella pneumoniae and Escherichia coli within hosts was estimated from hospital epidemiological data paired with mathematical modeling (Haverkate et al 2015).…”
Section: Hgt Is Understudied In Clinical Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although very little data are available regarding sources, mechanisms, or frequencies of ARG transfer between clinical reservoirs (Andersson and Hughes 2017), there are multiple cases in which the same ARG has been detected simultaneously on hospital surfaces and in patients (Hota et al 2009;Lowe et al 2012;Conlan et al 2014). Recently, the rate of bla OXA-48 plasmid transfer between Klebsiella pneumoniae and Escherichia coli within hosts was estimated from hospital epidemiological data paired with mathematical modeling (Haverkate et al 2015).…”
Section: Hgt Is Understudied In Clinical Environmentsmentioning
confidence: 99%
“…Bacterial population density and cell proximity differentially impact the various mechanisms of HGT. Bacteria that occupy the same environment, such as human intestines or sink surfaces, are more likely to share DNA via direct cell-to-cell transfer processes such as conjugation (Andersson and Hughes 2017). Conversely, transducing bacteriophage particles provide protection for DNA and support its persistence.…”
Section: Detecting and Anticipating Hgtmentioning
confidence: 99%
See 1 more Smart Citation
“…ICEs often carry resistance genes, for example Tn 916 family members that encode tetracycline resistance ( Roberts and Mullany, 2011 ). The known conditions for resistance gene transfer by conjugation include high density settings, such as the human or animal gut, biofilms, hospitals, and co-infection conditions ( Weigel et al, 2003 ; Savage et al, 2013 ; Huddleston, 2014 ; Andersson and Hughes, 2017 ). Although some resistance determinants have been plasmid-associated for a long time ( Barlow and Hall, 2002 ), others are mobilized to plasmids from chromosomes, and the rate at which these genes are being mobilized has increased since the widespread use of antibiotics about 70 years ago ( Barlow et al, 2008 ).…”
Section: Role Of Hgt In Transfer Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…Recent studies have shown that antibiotic concentrations significantly below the minimum inhibitory concentration for sensitive bacteria can be selective ( Gullberg et al, 2011 , 2014 ). Moreover, other contaminants, such as heavy metals, can also co-select for antibiotic resistance ( Pal et al, 2015 ; Andersson and Hughes, 2017 ).…”
Section: Enrichment Of Antibiotic Resistance Genesmentioning
confidence: 99%